Germany - Schanz, Sonja (Hodder Children's Books, London, 2002)
The peoples of East Germany and West Germany lived very different lives. In 1990, Germany was reunited and its people faced the task of building one nation. This book provides a picture of Germany. It includes maps and graphic panels showing statistics and fact boxes about size, flag, population, religion, currency and language.
Keywords: History